2015
DOI: 10.1016/j.apsusc.2014.12.171
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of surface coatings on a conductive substrate by controlled motion of graphene nanoflakes in a liquid medium

Abstract: Controlled motion of graphene and graphene oxide nanoflakes in a thin liquid film on metal surfaces was studied to unravel the significant variations of the electric field effects on the nanoparticles. It was found that graphene oxide flakes were negatively charged and migrated toward anode while the electrically neutral graphene flakes moved toward cathode. Therefore, thin layers of graphene as a protective coating were produced to inhibit corrosion of underlying metals and reduce friction and wear-related me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is found that direct current electric field drives multiwall carbon nanotubes move toward negative electrode and alternating current electric field can align the nanotubes in liquid solutions 12 . Our previous researches shown that electric field can drive spherical particles to move toward a wall from the inner position in liquid metal 19 and can drive graphene nanoflakes to move toward the negative electrode 20 . It is also demonstrated recently that electric field can help to breakup droplets into fine particles 21 and rotate crystals’ orientation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that direct current electric field drives multiwall carbon nanotubes move toward negative electrode and alternating current electric field can align the nanotubes in liquid solutions 12 . Our previous researches shown that electric field can drive spherical particles to move toward a wall from the inner position in liquid metal 19 and can drive graphene nanoflakes to move toward the negative electrode 20 . It is also demonstrated recently that electric field can help to breakup droplets into fine particles 21 and rotate crystals’ orientation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The aligned carbon nanotubes are desirable in the replacement of the damaged nerves in biological experiments [4]. The aligned graphene is desirable in surface coating [5]. Carbon nanotube is a rod-like geometry.…”
Section: Introductionmentioning
confidence: 99%